2019
DOI: 10.1002/gcc.22762
|View full text |Cite
|
Sign up to set email alerts
|

PRRX‐NCOA1/2 rearrangement characterizes a distinctive fibroblastic neoplasm

Abstract: Fibroblastic/myofibroblastic neoplasms represent a broad, and occasionally diagnostically challenging, category of soft tissue neoplasms. A subset of these tumors defy conventional classification. However, with the advent of next‐generation sequencing, the identification of disease‐defining molecular alterations is gradually improving their subclassification. Following identification of two index cases of a distinctive fibroblastic neoplasm with a fusion gene involving PRRX1 and NCOA1, we performed a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…The breakpoint of MEIS1 exon 7 fused to NCOA1 exon 13 is the same as one of the common fusion variants of MEIS1-NCOA2 fusions, and both preserve the C-terminal transcription activation domains of NCOA proteins in the deduced chimeric MEIS1-NCOA protein. Similar interchangeable role of NCOA1 and NCOA2 fusions has also been observed in other tumors, such as biphenotypic sinonasal sarcoma (PAX3-NCOA1/2) [7,8], PRRX-NCOA1/2 rearranged fibroblastic neoplasm [9], and uterine tumor resembling ovarian sex cord tumor (GREB1-NCOA1/ 2) [10].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The breakpoint of MEIS1 exon 7 fused to NCOA1 exon 13 is the same as one of the common fusion variants of MEIS1-NCOA2 fusions, and both preserve the C-terminal transcription activation domains of NCOA proteins in the deduced chimeric MEIS1-NCOA protein. Similar interchangeable role of NCOA1 and NCOA2 fusions has also been observed in other tumors, such as biphenotypic sinonasal sarcoma (PAX3-NCOA1/2) [7,8], PRRX-NCOA1/2 rearranged fibroblastic neoplasm [9], and uterine tumor resembling ovarian sex cord tumor (GREB1-NCOA1/ 2) [10].…”
Section: Discussionsupporting
confidence: 54%
“…NCOA2 gene encodes a nuclear hormone receptor transcriptional coactivator. Gene fusions involving NCOA2 with other partner genes have been identified in several distinct groups of mesenchymal tumors, including mesenchymal chondrosarcoma (HEY1-NCOA2) [4], soft tissue angiofibroma (AHRR-NCOA2) [5], congenital/infantile spindle cell RMS (VGLL2-NCOA2, SRF-NCOA2, TEAD1-NCOA2) [6], biphenotypic sinonasal sarcoma (PAX3-NCOA1/2) [7,8], PRRX-NCOA1/2 rearranged fibroblastic neoplasm [9], and uterine tumor resembling ovarian sex cord tumor (ESR1-NCOA2/3, GREB1-NCOA1/2) [10]. Our uterine case did not show sexcord-like differentiation as seen in uterine tumor resembling ovarian sex cord tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified C11orf95-NCOA1/2 in three ELTMDs. Fusion genes involving NCOA1/2 have been recurrently identified in several types of soft tissue tumors and acute leukemia (33,34). In the CNS, the case of ST anaplastic ependymoma presenting clear cell morphology with C11orf95-NCOA1 was reported (5).…”
Section: C11orf95 Exon 5 (Partial)mentioning
confidence: 99%
“…Arguably, the classification of fibroblastic tumours has undergone the most significant changes over the past decade, with the rise and fall of solitary fibrous tumour and fibrosarcoma, respectively, 6 and the recognition of new morphologically and genetically distinctive entities, including angiofibroma of soft tissue, 7 superficial CD34‐positive fibroblastic tumour, 8 and EWSR1 :: SMAD3 fibroblastic tumour 9 . Very recently, two other distinctive subsets of fibroblastic tumour have been identified, characterised by rearrangements involving KMT2A 10–12 and PRRX :: NCOA1 / 2 fusions, 13 respectively.…”
Section: Kmt2a‐rearranged Sarcoma and Prrx::ncoax Fibroblastic Tumoursmentioning
confidence: 99%